Relationship between the approval of the adoption of children by homosexuals and the attitude towards homosexuality among medical students and graduates: Relación entre la aprobación de la adopción de hijos por homosexuales y la actitud frente a la homosexualidad en estudiantes y egresados de medicina - Tipula Mamani, Marco A. (2021)
Introduction. Due to changes in the composition of the family and society, the adoption of children by homosexuals is becoming more frequent. It has been found that opposition to this request is often associated with homophobia. In Peru, no studies exist on these aspects. Objective: To determine the correlation between adoption approval and attitude towards homosexuality in medical students and graduates, Lima, Peru. Method: The observational and cross-sectional study was carried out. 205 people over 21 years of age participated. The Attitude Toward Homosexuality Scale (EAH-10) and the question “Should homosexual couples be allowed to adopt children like heterosexual couples?” were used. The relationships were made with the Pearson (r) and Spearman (rs) correlation coefficient. Results: Quantitatively, a negative and significant correlation was found between the response with the attitude towards homosexuality (r = -0,727; rs = -0,718) and a positive and significant correlation with the number of homosexual friends (r = 0,402; rs = 0,399). 57,6% indicated approval of the question posed. Greater intolerance attitudes were found in men than in women (r = 0,328; p = 0,000). A multiple linear regression model showed that attitude towards homosexuality, sex, and number of homosexual friends are good predictors of acceptance of homosexual adoption. Conclusion: The response was significantly correlated with attitudes of homophobia and with the number of homosexual friends. Furthermore, homophobic attitudes were higher in men.